PENINGKATAN PRODUKTIVITAS SEL SURYA DENGAN MEMANFAATKAN PARABOLA SEBAGAI KONSENTRATOR - Sigit Iswahyudi; Kun Suharno; Agung Trihasto (Prosiding SNST Fakultas Teknik, 2010)
Solar cell is engineered to convert photon energy of the sun that the earth get it on terrestrial zone. Usually, in laboratory, solar cell will be irriadiated by 1 kW/m2 constant photon source to standardize the product and photovoltaic energy become the output. The productivity of solar cell then be restricted by the photon energy input.In this discussion, the productivity of solar cell will be enhanced by using parabolic concentrator. The restriction of input is broken down by raising the intensity of photon radiation.Key words: solar radiation, parabolic concentrator, solar cell, photovoltaic energy